2017
DOI: 10.1021/acsami.7b01365
|View full text |Cite
|
Sign up to set email alerts
|

“One-for-All”-Type, Biodegradable Prussian Blue/Manganese Dioxide Hybrid Nanocrystal for Trimodal Imaging-Guided Photothermal Therapy and Oxygen Regulation of Breast Cancer

Abstract: Multimodal imaging-guided diagnosis and therapy has been highlighted in the area of theranostic nanomaterials. To provide more suitable theranostic candidates, Prussian blue (PB)/manganese dioxide (MnO) hybrid nanoparticles (PBMn) smaller than 50 nm are prepared by a one-pot method. MnO, which is reduced from KMnO, not only controls the particle size, the optical properties, and the transverse relaxation rate (r) of PB but also enhances the catalysis efficacy of PB to HO for oxygen generation. PBMn can serve a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 53 publications
4
74
0
Order By: Relevance
“…In our previous work, we observed that PTT can efficiently inhibit the growth of primary tumors and further confirmed that photothermal therapy can effectively enhance chemotherapy . The enhancement may be chiefly related to the immune response induced by PTT.…”
Section: Introductionsupporting
confidence: 60%
“…In our previous work, we observed that PTT can efficiently inhibit the growth of primary tumors and further confirmed that photothermal therapy can effectively enhance chemotherapy . The enhancement may be chiefly related to the immune response induced by PTT.…”
Section: Introductionsupporting
confidence: 60%
“…of CDs/MnO 2 -PEG nanohybrids. This finding indicated that the CDs/MnO 2 -PEG nanohybrids accumulated in the tumor area because of the enhanced permeability and retention (EPR) effect and the gradual reduction of MnO 2 into Mn 2+ in the mildly acidic TME [61,62]. The MR signal intensity at the tumor site reached a fastigium at 12 h p.i.…”
Section: In Vivo Mr/fl Imaging and Real-time Biodistributionmentioning
confidence: 93%
“…As reported, tumor cells perform unique metabolic mode different from normal cells . On one hand, malignant tumor cells produce excessive amounts of H 2 O 2 , which leads to a significantly increased level of H 2 O 2 in TME . On the other hand, the upregulated glycolytic metabolism during tumorigenesis generates massive lactic acid, which results in an acidic TME with low pH value .…”
Section: Introductionmentioning
confidence: 94%